Prevalence of obesity amongst bank employees in Latur city of Maharashtra, India - Kulkarni, Pramod P.; Gaikawad, Bhaskar S.; Takalkar, Anant A.; Bhise, Mukund D. (International Journal Of Community Medicine And Public Health, 2019)
Background: India is currently experiencing rapid epidemiological transition with rising prevalence of obesity which may be due to sedentary lifestyle and changing dietary pattern. Certain occupations like the job of bank employees are sedentary which predispose individuals to obesity. Hence the present study was carried out to study the prevalence of obesity in bank employees in Latur city of Maharashtra. Methods: A cross-sectional study was carried out amongst 400 bank employees of Latur city. Banks were listed according to sectors i.e. government, co-operative and private. The study subjects were interviewed by predesigned and pretested proforma including bio-social characteristics like age, gender, height, weight etc. The anthropometric measurements were taken like height, weight etc. Data was entered in Microsoft Excel and analysed by using appropriate test whenever necessary. Results: According to body mass index (BMI) classification by WHO classification 34.5% subjects were overweight and obese and 25.75% of bank employees had obesity by waist-hip ratio as per WHO classification and 18.5% of bank employees had isolated abdominal obesity. Conclusions: The prevalence of generalized as well as abdominal obesity by WHO classification was more in bank employees. The associated risk factors like age, gender and designation was found to be significant.